Rapid versus slow rate advancement of feeds for enterally fed extremely low birth weight infants < 1000g: randomised controlled trial - Raban, Moegammad Shukri (Department of Paediatrics and Child Health, 2015)
Background The timeous achievement of full enteral nutrition in a preterm infant is a critical prerequisite for optimal growth, neurodevelopment and long-term wellbeing. However, the optimal enteral feeding regimen for preterm infants has not been established, and wide variations occur in practice. The debate on the most appropriate feeding strategy is nuanced by studies suggesting that early introduction of enteral feeds and the rapid advancement of enteral feeds may increase the risk of feeding intolerance and may be involved in the pathogenesis of necrotising enterocolitis (NEC). Objective 1. To review randomised controlled trials (RCT); examining the effect that the rate of advancement of enteral feeds has on the incidence of; NEC, mortality, growth, health care utilisation and other morbidities in very low birth weight (VLBW) and extremely low birth weight (ELBW) infants. 2. To establish the safety and efficacy of commencing enteral breast milk feeds at 24 ml/kg/day on the day of birth and advancing enteral breast milk feeds at 36 ml/kg/day, in infants weighing â‰¤ 1000 g.